1.докажите неравеноа) (х-2) > х(х-4); ​

DKNRMLLY DKNRMLLY    1   07.05.2019 06:53    2

Ответы
Санжик707 Санжик707  07.05.2019 07:50

( х - 2 ) > х ( х - 4 )

х - 2 = х² - 4х

- х² - 4х - х + 2 = 0

- х² - 5х + 2 = 0

d = ( - 5 ) ² - 4 • ( - 1 ) • 2 = 25 + 8 = 33 , d > 0 , уравнение имеет 2 корня .

d = \frac{ - ( - 5) +33}{2( - 1)} = \frac{28}{ - 2} = - \frac{28}{2} = - 14.

d = \frac{ - ( - 5) - 33}{2( - 1)} = \frac{ - 28}{ - 2} = 14.

ответ :

 - 14

14

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра